2022
DOI: 10.1039/d1sc06134h
|View full text |Cite
|
Sign up to set email alerts
|

Persistent nucleation and size dependent attachment kinetics produce monodisperse PbS nanocrystals

Abstract: Modern syntheses of colloidal nanocrystals yield extraordinarily narrow size distributions that are believed to result from a rapid “burst of nucleation” (La Mer, JACS, 1950, 72(11), 4847–4854) followed by diffusion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 39 publications
(64 reference statements)
1
21
1
Order By: Relevance
“…We have observed similarly prolonged nucleation under identical conditions using in situ X-ray scattering measurements that will be reported elsewhere. 44 The increasing nanocrystal concentrations observed here provide a direct measure of the nucleation kinetics because the final nanocrystals do not significantly ripen or agglomerate under these conditions. 26,30 Hence, the steadily increasing [NC] shows that crystal nucleation continues throughout a significant fraction of the total reaction time rather than occurring in a burst.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…We have observed similarly prolonged nucleation under identical conditions using in situ X-ray scattering measurements that will be reported elsewhere. 44 The increasing nanocrystal concentrations observed here provide a direct measure of the nucleation kinetics because the final nanocrystals do not significantly ripen or agglomerate under these conditions. 26,30 Hence, the steadily increasing [NC] shows that crystal nucleation continues throughout a significant fraction of the total reaction time rather than occurring in a burst.…”
Section: Resultsmentioning
confidence: 80%
“…A similar conclusion is reached in a related study on PbS to be published elsewhere. 44 More detailed understanding of the factors controlling the growth rate would, therefore, enable the rational optimization of size distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this ligand-based approach allows us to fine-tune particle size over a wide range and is applicable to both monosulfide and monoselenide compositions, with little to no variation in other synthetic conditions. This mixed precursor approach to fine-tune particle size is a versatile addition to the synthetic nanochemistry toolbox, which nicely complements other available methods for controlling particle size of colloidal nanocrystals. ,, …”
Section: Resultsmentioning
confidence: 99%
“…This mixed precursor approach to fine-tune particle size is a versatile addition to the synthetic nanochemistry toolbox, which nicely complements other available methods for controlling particle size of colloidal nanocrystals. 26,47,48 Spectroscopic Analysis of Surface Ligand Coordination. The infrared spectra of all the binary alkaline-earth chalcogenides show vibrations consistent with the presence of carboxylate ligands (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…146 These mechanisms link the narrow polydispersity to a brief period of nucleation that precedes growth and a growth process that is limited by diffusion of monomers to the nanocrystals surface, and a homogeneous ripening process that broadens the polydispersity while increases the average size. However, recent kinetics investigations of InP, 150 CdSe, 151 PbS and PbSe 129,152 QD syntheses have observed long nucleation periods that in some cases continue throughout the synthesis and are concurrent with growth, as well as attachment limited growth kinetics that support size distribution focusing. Indeed, a recent comprehensive review of semiconductor, metal, and oxide nanoparticle formation concluded that, "compelling evidence for burst nucleation and diffusion-controlled growth in semiconductor nanoparticle formation is missing" and "a primary working hypothesis going forward to test and to try to disprove, is that nucleation may well more often be continuous".…”
Section: -Growth Mechanisms That Support Narrow Polydispersitiesmentioning
confidence: 99%